2012
DOI: 10.1021/ja211027m
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanism of ATP Hydrolysis in F1-ATPase Revealed by Molecular Simulations and Single-Molecule Observations

Abstract: Enzymatic hydrolysis of nucleotide triphosphate (NTP) plays a pivotal role in protein functions. In spite of its biological significance, however, the chemistry of the hydrolysis catalysis remains obscure because of the complex nature of the reaction. Here we report a study of the molecular mechanism of hydrolysis of adenosine triphosphate (ATP) in F(1)-ATPase, an ATP-driven rotary motor protein. Molecular simulations predicted and single-molecule observation experiments verified that the rate-determining step… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
134
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 94 publications
(150 citation statements)
references
References 53 publications
(113 reference statements)
16
134
0
Order By: Relevance
“…The connection between binding and release events to the rotation of the γ shaft has been investigated by several groups using structural calculations (30)(31)(32)(33)(34)(35). A question arising from our study that simulations could treat is the evolution of the hydrogen-bonding network during structural displacements of a β subunit, and how it is affected by the presence of the binding nucleotide.…”
Section: Discussionmentioning
confidence: 99%
“…The connection between binding and release events to the rotation of the γ shaft has been investigated by several groups using structural calculations (30)(31)(32)(33)(34)(35). A question arising from our study that simulations could treat is the evolution of the hydrogen-bonding network during structural displacements of a β subunit, and how it is affected by the presence of the binding nucleotide.…”
Section: Discussionmentioning
confidence: 99%
“…As noted earlier, the present formulation of the model is not intended to apply to the ATP hydrolysis step, which is believed to involve two or more substeps, rather than just one (28,30,50). An α of 0.83 for ATP hydrolysis in tyrosyl-tRNA synthase was inferred by use of mutants, and an explanation of this high α for this reaction, where overall ΔG 0 is small, was given by Warshel, who postulated two transition states of about equal energy with a shallow minimum in between (28).…”
Section: Concluding Discussion and Outlookmentioning
confidence: 99%
“…Thereby the first step had a barrier almost equal to the energy to reach the shallow well, and so α was close to unity. Electronic structure calculations in F 1 -ATPase of a more ab initio nature (30,50) indicated at least two TS's, but further studies are needed to explore these TS's, and the valley between them should be treated. Obtaining α via stalling experiments has an advantage over obtaining it via mutations because the latter may also affect λ.…”
Section: Concluding Discussion and Outlookmentioning
confidence: 99%
See 1 more Smart Citation
“…The glutamic acid general base has been thought to activate the intervening water molecule to induce nucleophilic attack of the water molecule on the ␥ phosphate. Recent quantum chemical calculation and single-molecule analysis revealed that the role of general base may be not water activation but the enhancement of proton transfer from phosphoester to bulk solution (135). In some ATPases the glutamic acid also plays a role as a sensor for the ATP binding state and changes orientation drastically upon ATP binding (136).…”
Section: Motion Mechanism Energy Conversion: Transition Among Entropymentioning
confidence: 99%